Influence of bioregulator on physiological quality of maize seed during storage - Dan, Lilian Gomes de Moraes; Braccini, Alessandro de Lucca; Piccinin, Gleberson Guillen; Dan, Hugo de Almeida; Ricci, Thiago Toshio; Scapim, Carlos Alberto (Comunicata Scientiae, 2014)
Incorporation of vegetal regulator-based products to maize seeds is a new reality. However, special attention should be paid to the physiological quality of seeds, particularly during storage. The purpose of the present study was to assess the effects of the bioregulator Stimulate® via both seed treatment and maize seeds’ physiological quality in different storage periods. Evaluation of physiological quality was accomplished by germination test (first and final count), cold germination test and sand emergence test. Maize seeds’ bioregulator-managed treatment – especially when applied to high vigor seeds – ensures lower reduction in physiological quality for up to 180 days of storage, whereas, when applied to medium vigor seeds, greater bioregulator benefits are observed in short-term storage.